Acceptance, attitude and knowledge towards agriculture economic activity between rural and urban youth: the case of contract farming - Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak (Asian Network for Scientific Information, 2010)
This study attempts to investigate whether rural and urban youth have any difference on acceptance, attitude and knowledge towards contract farming. Agriculture indeed has been an important factor for development in Malaysia. Contract farming is one of the agricultural activities which is still in its infancy stage in Malaysia that offers huge benefits for the interested parties. Youth acceptance, attitude and knowledge can be considered as the key for this new industry to be sustained, but do youth in Malaysia have a good level of acceptance, attitude and knowledge towards contract farming? Data was gathered through a survey questionnaire on a total of 400 rural and urban youth who are currently studying in various tertiary institutions throughout Malaysia. Data were analyzed using SPSS where analyses such as frequency, mean, standard deviation and independent sample t-test were performed. Interestingly, urban and rural youth have similar level of acceptance, attitude and knowledge towards contract farming. Based on the independent sample t-test, there is no significant difference in acceptance, attitude and knowledge on contract farming between rural and urban youths. Based on the results, it can be concluded that contract farming can be a mechanism to attract more urban and rural youth to be part of agriculture community in Malaysia. To do this, more promotion and information on contract farming should be exposed to the youths. It is recommended that agriculture agencies and agriculture related universities to take the responsibilities of introducing the concept of contract farming to the youth.